Development of drive and control system module for surface unmanned vehicle - Syazwan Hakim, Mat Shahar (2022)
A surface unmanned vehicle (SUV) is a vehicle that is driven without the presence of a crew. Handle in a variety of methods, including remotely through a remote control or automatically via autonomous navigation. Surveying using a manned vehicle may be expensive, especially if a passenger or crew is required, and it is limited to risky tasks that could endanger the passenger or crew, such as hazardous or enclosed areas. With unmanned qualities, a remote-operated unmanned vehicle can complete the work more inexpensively and efficiently. The SUV is an alternate feature for a surface vehicle, such as a boat or ship, that can be handled remotely and has some self-driving capabilities. Nonetheless, the bulk of currently available commercial SUVs have expensive pricing, either because to the brand or the size of the market, which has yet to reach the required product level. As a result, this project has taken the lead in developing a low-cost SUV boat with a basic design based on the catamaran concept. Polyvinyl Chloride (PVC) plastic parts are used to make two hulls, while polystyrene is used to build the body. This project also includes a wireless remote control with radio frequency (RF) transmission, real-time viewing on a surface water vehicle, and a Global Positioning System (GPS) unit to configure the SUV's coordinate location using Global System for Mobile Communication/General Packet Radio Service (GSM/GPRS) technology to upload the data information into customizable graphical user interface (GUI) software. The SUV's propulsion controller unit has been built remotely, and this technology also includes operating the vehicle's rudder for tilting its motion. The project's goal is to create a prototype mini-SUV with long-range wireless control and monitoring for the calm and low-tidal water area.